Effect of HIV treatment and other risk factors on cardiovascular disease risk in rural South Africa - Mudombi, Wisdom Forward (My University, 2019)
Background. Cardiovascular disease (CVD) is increasing in resource-limited settings. Few studies on the effect of combination antiretroviral treatment (cART) on CVD have been conducted in rural HIV-infected populations. There is need to further identify CVD risk burden and to estimate the influence of cART on CVD risk. This study assesses the CVD risk using the reduced Data Collection on Adverse Effects of Anti-HIV Drugs (D:A:D) CVD risk score and determines the effect of current and previous cART on the D:A:D risk score in HIV-positive participants in a rural African HIV-positive population. In addition the study identifies which determinants not accounted for in the original D:A:D risk score within a rural HIV-positive cohort are significantly associated with the D:A:D risk score. Methods. A cross sectional analysis was performed including baseline data of all HIVpositive participants of the Ndlovu cohort study. This is a longitudinal study in rural South Africa including 1927 adults (46% HIV-positive) evaluating the influence of HIV on the development of CVD. Data were collected on demographics, education, cardiovascular risk factors, HIV and cART related characteristics. The reduced D:A:D score was calculated using the updated prediction model and multivariable regression was performed to determine associations with the D:A:D score. Results. 885 participants (59.6% females) were included. The mean age was 42 years (standard deviation (SD) 10.3). 186(21%) were cART naïve and 699(79%) were already on cART. Median duration of cART use was 2.4 years (interquartile range (IQR) 0.0-6.8). The median D:A:D score was 2.2% (1.1-5.0); 2.4% (IQR 1.2-5.2) for participants on cART and 1.4% (IQR 0.7-3.5) for those not on cART (p<0.001). Factors associated with an increase in D:A:D score were male gender (0.987; 95% CI 0.851-1.122; p<0.001), no formal education (0.538; 95% CI 0.209-0.867; p<0.001), BMI (Overweight/obesity) (0.235; 95% CI 0.091- 0.380; p<0.001) and Albumin creatinine ratio (ACR) (0.0015; 95% CI 0.00044-0.0025; p=0.005). Conclusion. In this young HIV-positive rural African population 5-year CVD risk according to the D:A:D score is low. The risk is higher in participants on cART compared to that not on cART. Determinants of CVD risk are male gender, no formal schooling, and BMI and albumin/creatinine ratio. These factors have to be considered for preemptive interventions focused on the HIV infected population in order to reduce CVD morbidity and mortality.
research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in the field of Epidemiology and Biostatistics. Johannesburg, September 2019